Association of zinc serum level with metabolic syndrome in iranian children and adolescents: The CASPIAN-V study - Qorbani, Mostafa; Movasaghi, Negar; Mohammadian Khonsari, Nami; Daneshzad, Elnaz; Shafiee, Gita; Ashraf, Haleh; Sokoty, Leily; Mahdavi-Gorabi, Armita; Ebrahimi, Mehdi; Heshmat, Ramin; Kelishadi, Roya (Frontiers in Nutrition, 2022)
Introduction. Metabolic syndrome comprises a set of metabolic risk factors associated with cardiovascular disease and type 2 diabetes. Zinc plays an essential role in numerous enzyme functions that may be associated with metabolic dysfunctions. The relationship between serum Zinc levels and metabolic syndrome in adolescents has not been specifically studied. Therefore, the present study was performed to determine the relationship between serum Zinc levels and metabolic syndrome in Iranian children and adolescents. Methods. This cross-sectional study was performed using data collected in the CASPIAN-V study. In this project, data were collected using interviews, examinations, biochemical assessments, anthropometric studies, and the nutritional status of participants. The variables considered in the present study included serum Zinc levels, triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), fasting blood sugar, height, weight, abdominal circumference, and systolic and diastolic blood pressure. Results. A total of 1371 participants were included in this study, with a mean age of 12.24 ± 3.23 years. In total, 12.40% (n = 170) of the study population had metabolic syndrome, of which 55.7% were boys and 44.3% were girls. Mean Zinc levels (µg/dL) in patients with and without metabolic syndrome were 107.03 and 110.60, respectively (p-value = 0.211) and 111.80 for boys and 109.10 for girls (p-value = 0.677). Conclusion. This cross-sectional study showed no association between serum Zinc levels and metabolic syndrome in children. Further similar studies and cohort studies with large sample sizes are needed to reveal the exact relationship between serum Zinc levels and metabolic syndrome.